Role and architectural significance of porous chitosan-based scaffolds in bone tissue engineering - Lekhavadhani, Sundaravadhanan; Shanmugavadivu, Abinaya; Selvamurugan, Nagarajan (International journal of biological macromolecules, 2023)
In designing and fabricating scaffolds to fill the bone defects and stimulate new bone formation, the biomimetics of the construct is a crucial factor in invoking the bone microenvironment to promote osteogenic differentiation. Regarding structural traits, changes in porous characteristics of the scaffolds, such as pore size, pore morphology, and percentage porosity, may patronize or jeopardize their other physicochemical and biological properties. Chitosan (CS), a biodegradable naturally occurring polymer, has recently drawn considerable attention as a scaffolding material in tissue engineering and regenerative medicine. CS-based microporous scaffolds have been reported to aid osteogenesis under both in vitro and in vivo conditions by supporting cellular attachment and proliferation of osteoblast cells and the formation of mineralized bone matrix. This related notion may be found in numerous earlier research, even though the precise mechanism of action that encourages the development of new bone still needs to be understood completely. This article presents the potential correlations and the significance of the porous properties of the CS-based scaffolds to influence osteogenesis and angiogenesis during bone regeneration. This review also goes over resolving the mechanical limitations of CS by blending it with other polymers and ceramics.